Protection of indigenous peoples in situations of voluntary isolation (2021)
The presence of indigenous peoples in a situation of voluntary isolation or initial contact is a frequent phenomenon in the current era in the American continent; most of them are located in the Amazon rainforest. The regulation and legal protection of these communities, in a multicultural context, stands as a challenge for the law. For this reason, this article studies the provisions of Colombian and international legislation, aimed at protecting indigenous peoples in isolation, identifying and analysing the fundamental principles that govern their legal protection, namely: Free self-determination, no contact, special protection and territorial intangibility, which impose on the States the obligation to adopt adequate policies and measures, with the knowledge and participation of indigenous peoples and organizations, to recognize, respect and protect the territories and cultures of these peoples, as well as the guarantee of multiculturalism and respect for the will and self-determination of these peoples, concluding that it is a sui generis legal regime that endows these peoples with extraordinary rights and whose analysis warrants a detailed comparative law investigation in Latin American countries.